Prevalence of Psychiatric Morbidity Among Victims of Terrorist Attacks: Comparative Study - Haroon Rashid; Muhammad Rizwan (Journal of Management Practices, Humanities and Social Sciences, 2023)
To evaluate the occurrence of psychiatric morbidity Posttraumatic Stress Disorder (PTSD); mood state; (state of depression, anxiety, stress) and its effect on general health among victims of terrorist attacks (mild injuries, severe injuries & amputation) in Peshawar, Khyber Pakhtunkhwa. Current study was a cross-sectional correlational research applied on three groups of admitted patients; who were injured during attacks (with mild injuries, severe injuries & severe injuries along with amputation), the data were collected after one week of attack during from the patients who had direct exposure to terrorist attacks and sought treatment from Combined Military Hospital, Peshawar, Pakistan, during the period of November 2021 to September 2022. Sample included all the survivors who sought medical assistance from the hospital. The instruments comprised upon Impact of Event Scale Revised (IES-R 22), General Health Questionnaire (GHQ-12), and Depression, Anxiety and Stress Scale (DASS-21). PTSD has positive association with Depression, Anxiety and Stress but negative association with General Health Questionnaire among terrorists’ attack victims. The terrorist attack victims had significantly higher psychiatric morbidity than non-exposed participants. Psychiatric morbidity was found highest in the victims of survivors of bomb blasts.